Cognitive, social, and behavioral manifestations of the co-occurrence of autism spectrum disorder and attention-deficit/hyperactivity disorder: A systematic review. (May 2022) - Rosello, Rocio; Martinez-Raga, Jose; Mira, Alvaro; Pastor, Juan Carlos; Solmi, Marco; Cortese, Samuele
Attention-deficit/hyperactivity disorder is one of the most common comorbidities in individuals with autism spectrum disorder. However, the clinical implications of the co-occurrence of these two disorders are still poorly understood. Based on a preregistered protocol (PROSPERO CRD42020193880), this systematic review identified 34 articles, published between January 1, 2014, and September 1, 2020, on cognitive, adaptive/social, and behavioral manifestations in children and adolescents with a diagnosis of autism spectrum disorder and attention-deficit/hyperactivity disorder (ASD+). The majority of available studies found a tendency toward a significant poorer cognitive performance in individuals with ASD+ compared with those with autism spectrum disorder alone (ASD−). The analysis of social/adaptive processes suggested that ASD+ is associated with lower functioning in comparison with ASD−. Finally, individuals with ASD+ were more likely to develop emotional/behavioral difficulties, in particular externalizing problems. Although some studies did not find differences among the two groups, overall co-occurring ASD+ may constitute a distinctive phenotype with a greater likelihood of cognitive, adaptive dysfunction, and mental health symptoms compared with ASD−. These results may inform the setting up and implementation of care pathways for individuals with attention-deficit/hyperactivity disorder and autism spectrum disorder. Lay abstract: This work aimed to review recent research on the characteristics of individuals who have both autism spectrum disorder and attention-deficit/hyperactivity disorder due to their high co-occurrence. Thirty-four studies were analyzed and main findings summarized in two content domains focusing on areas that could enhance our understanding of the cognitive and behavioral characteristics of individuals with autism spectrum disorder + attention-deficit/hyperactivity disorder (ASD+). Most of the results suggested that ASD+ is a co-occurring condition associated with more severe impairments in cognitive functioning, adaptive behavior, and increased likelihood to present more emotional/behavioral problems. These results will be helpful to provide improved care plans for individuals with both attention-deficit/hyperactivity disorder and autism spectrum disorder.